Experimental Study on The Effect of Cross Feed of Surface Grinding on the Vibration and the Surface Roughness of Hardened Tool Steel OCR12VM - Anam, Chairul; Muzaka, Khairul; Pamuji, Dian Ridlo (Jurnal Rekayasa Mesin, 2020)
The grinding process is a machining process to obtain qualified surface roughness levels and high dimensional accuracy. There are two types of processes in the grinding process, namely the roughening and finishing processes. The vibration effect of the roughing process can damage and shorten the life of the tool/machine, while in the finishing process, the effect of vibration will reduce the dimensional accuracy, shape, and surface smoothness of the workpiece. This study aims to determine the effect of crossfeed on the amplitude of vibration and surface roughness of the workpiece on the surface grinding process. The materials used are hardened tool steel OCR12VM with a variety of grinding stone types A46QV and A80LV made of aluminum oxide. The Variables of process parameters are crossfeed (mm / step) and depth of cut (mm). The measurement of vibrations uses an accelerometer, which is processed by the math CAD program in the form of amplitude and frequency. For surface roughness measurements, it is used the MT-301 surface test with 5 sample points and a sample length of 0.8 mm. The results show that the greater the cross-feed value, the bigger the amplitude of the vibration level and the surface roughness of the workpiece. The magnitude of the amplitude of the vibration on the acceleration that occurs in the grinding stone type A46QV starts from 6,7369 -18.7525 g.rms, while the grinding stone type A80LV starts from 5.0904 g.rms to 18.2821 g.rms. The surface roughness achieved in both grit 46 and grit 80 is from N3 to N5.